2008
DOI: 10.1016/j.molcel.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin Protein 1a Stimulates Histone H3 Lysine 36 Demethylation by the Drosophila KDM4A Demethylase

Abstract: Summary Recent discoveries of histone demethylases demonstrate that histone methylation is reversible. However, mechanisms governing the targeting and regulation of histone demethylation remain elusive. Here we report that a Drosophila melanogaster JmjC domain-containing protein, dKDM4A, is a histone H3K36 demethylase. dKDM4A specifically demethylates H3K36me2 and me3 both in vitro and in vivo. Affinity purification and mass spectrometry analysis revealed that Heterochromatin Protein 1a (HP1a) associates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
100
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 65 publications
6
100
0
1
Order By: Relevance
“…In agreement with a euchromatin function, HP1a targets to highly expressed genes, including developmentally regulated genes and Hsp70, where it controls gene expression after heat shock (Biasin et al 2003). Moreover, recent studies have shown that HP1a is a positive regulator of transcription by facilitating H3K36 demethylation at active and/or heterochromatic regions (Lin et al 2008), and that it positively regulates euchromatic gene expression by interacting with RNA transcripts and hnRNPs (heterogeneous nuclear ribonucleoproteins) in Drosophila (Piacentini et al 2009). These data suggest that, in addition to its function in gene silencing, HP1 might also play an activating role in gene regulation.…”
mentioning
confidence: 89%
“…In agreement with a euchromatin function, HP1a targets to highly expressed genes, including developmentally regulated genes and Hsp70, where it controls gene expression after heat shock (Biasin et al 2003). Moreover, recent studies have shown that HP1a is a positive regulator of transcription by facilitating H3K36 demethylation at active and/or heterochromatic regions (Lin et al 2008), and that it positively regulates euchromatic gene expression by interacting with RNA transcripts and hnRNPs (heterogeneous nuclear ribonucleoproteins) in Drosophila (Piacentini et al 2009). These data suggest that, in addition to its function in gene silencing, HP1 might also play an activating role in gene regulation.…”
mentioning
confidence: 89%
“…dsRNAs targeting LacZ or enok were synthesized as described previously (Lin et al 2008). S2 cells were seeded at 1 3 10 6 cells per milliliter in serum-free Schneider's insect medium for RNAi treatment.…”
Section: Rnai Knockdown In S2 Cellsmentioning
confidence: 99%
“…HP1a interactors have been identified previously using yeast two-hybrid screens (Shaffer et al 2002;Giot et al 2003), and HP1a has been recovered from pull-downs of several chromatin-associated protein complexes (Badugu et al 2003;Lin et al 2008;Emelyanov et al 2010;Nozawa et al 2010). HP1a also has been analyzed by inducible expression, affinity purification, and mass spectrometry (Lin et al 2008;Ryu et al 2014).…”
mentioning
confidence: 99%
“…HP1a also has been analyzed by inducible expression, affinity purification, and mass spectrometry (Lin et al 2008;Ryu et al 2014). However, a comprehensive picture based on HP1a expressed at endogenous levels within the organism has been lacking.…”
mentioning
confidence: 99%